Ferromagnetic correlations in heavy fermions from an NMR point of view: YbNi4P2 vs. YbRh2Si2. Issue 3 (18th February 2013) - Baenitz, M.; Sarkar, R.; Khuntia, P.; Krellner, C.; Geibel, C.; Steglich, F.; Toropov, Alexey; Ivanov, Sergey
Abstract Ferromagnetic correlations are discussed on the basis of shift K4f and spin–lattice‐relaxation (SLR) rate R4f(T) = (1/T1T)4f investigations for YbNi4P2 and YbRh2Si2. For YbRh2Si2 the coexistence of antiferromagnetic (afm) and ferromagnetic (fm) fluctuations at the edge of magnetic order is strongly related to the non‐Fermi‐liquid behaviour (NFL). The analysis of the NMR results for YbNi4P2 in the modified Korringa framework for correlated local moment metals yields the enhancement factor <![CDATA[$\cal K$]]> <inline-graphic xlink:href="ark:/27927/pgh6nd2hr2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(α) which is a measure of the q ‐space dependence of the complex dynamic susceptibility. Surprisingly the <![CDATA[$\cal K$]]> <inline-graphic xlink:href="ark:/27927/pgh6nd2hqj" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(α) behavior of YbNi4P2is very similar to YbRh2Si2and evidences strongly the evolution of an afm (q ≠ 0) component in the q = 0 dominated complex dynamic susceptibility χ'' (q, ωn, T) at low temperatures and in small fields. This suggests the presence of ferro‐ and antiferromagnetic fluctuations at the QCP and the freezing out of the afm ones by applying magnetic fields and tuning towards FL state. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)